Conservation biology of cheetahs Acinonyx jubatus (Schreber 1775) and African wild dogs Lycaon pictus (Temminck 1820) in South Africa - Somers, Michael J. (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.